2017
DOI: 10.1111/ivb.12199
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic scaling in modular animals

Abstract: Abstract. Metabolic scaling is the relationship between organismal metabolic rate and body mass. Understanding the patterns and causes of metabolic scaling provides a powerful foundation for predicting biological processes at the level of individuals, populations, communities, and ecosystems. Despite intense interest in, and debate on, the mechanistic basis of metabolic scaling, relatively little attention has been paid to metabolic scaling in clonal animals with modular construction, such as colonial cnidaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 111 publications
(352 reference statements)
2
51
0
Order By: Relevance
“…Modular animals are useful for testing theories of metabolic scaling, as it is possible to manipulate their size and shape (reviewed in Burgess et al., ). In a colonial ascidian, Nakaya, Saito, and Motokawa () found that metabolic scaling switched from allometry to isometry during the takeover stage of the colony, in which the zooids of the parent generation in a colony degenerate and zooids of a new generation develop in unison.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Modular animals are useful for testing theories of metabolic scaling, as it is possible to manipulate their size and shape (reviewed in Burgess et al., ). In a colonial ascidian, Nakaya, Saito, and Motokawa () found that metabolic scaling switched from allometry to isometry during the takeover stage of the colony, in which the zooids of the parent generation in a colony degenerate and zooids of a new generation develop in unison.…”
Section: Discussionmentioning
confidence: 99%
“…Modular animals are useful for testing theories of metabolic scaling, as it is possible to manipulate their size and shape (reviewed in Burgess et al, 2017). In a colonial ascidian, Nakaya, Saito, and…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In keeping with the overall theme of my article, this discovery of metabolic scaling diversity was rediscovered many times during the 1900s (e.g., [23,32,[261][262][263]), but largely ignored in favor of a 3/4-power law. Only during the last two decades, has a true appreciation of the broad diversity of metabolic scaling relationships been spreading widely (see e.g., [19,20,24,26,27,33,34,39,44,46,50,[54][55][56][57][58]103,[105][106][107]117,118,121,132,142,143,147,149,153,182,193,219,225,260,264,265]), thus helping to stimulate the development of multi-mechanistic explanatory models (see Section 3.1). The recognition of diversity is not necessarily a hindrance to the development of general theory, as sometimes thought (cf.…”
Section: The Diversity Of Metabolic Scalingmentioning
confidence: 99%